The articulation of anti-Asian sentiment in America: Frames in BTS’ tweet and press release - Maru, Mister Gidion; Kinanti, Dewi; Andries, Fivy A; Kimbal, Rahel W (EduLite: Journal of English Education, Literature and Culture, 2023)
Despite the Covid-19 pandemic has been considered being over, yet it remains to leave global traces of reaction including in America. This study aims at investigating Anti-Asian Sentiments in Bangtan Sonyeondan (BTS)’ Tweet and Press Release. Basing upon the curiosity of how the that particular sentiment spread in America and the reaction toward it from the perspective of the Asian. This study applies a qualitative method relying upon the data taken from an officially transcribed texts of short press the release video by Bangtan Sonyeondan (BTS)’ in YouTube as display in the White House website and Bangtan Sonyeondan (BTS)’ tweets posted to support Stop Asian Hate Movement. The analysis employs Huckin's Critical Discourse Analysis theory The results show that sentiment frames emerge in the forms of the violent attacks, discrimination, and the degradation of self-esteem. The existence of such sentiments has encouraged some reactions namely the awareness of Asian identity, the awareness of the rise of hate crimes, and the awareness of of supporting Stop Asian Hate movement. These findings implies that the BTS expressions language can act as an instrument of advocacy, power of negotiation, and expression of ideology. Thus, this study is significant for further studies on text analysis and rhetoric expressions, and cultural studies in general.